Influence of physical fitness on decision-making of soccer referees throughout the match - Castillo-Rodríguez, Alfonso; Alejo-Moya, Emilio; Figueiredo, Antonio; Onetti, Wanesa; González-Fernández, Francisco Tomás (Heliyon, 2024)
The purpose of this study was to analyze the relationships between physical fitness and physical performance in competition and the decision-making (successes and errors). A sample of 22 male national-level soccer referees (weight: 72.7 kg; height: 178.0 cm; age: 23.4 years) participated in this study. Physical fitness was assessed through 6 series of 40 m (velocity) and Yo-yo (aerobic) test in annual exam by Soccer Committee, physical performance was performed through the total distance covered in competition (Experiment 1), and decision-making was registered through a simulated Video Assistant Referee system (VAR) with the consensus of 2 national referees evaluating only warnings (yellow cards), expulsions (red cards), established penalties and obvious goal actions (called and no called) (Experiments 2 and 3). Results showed that physical fitness test was related with total distance (rho = 0.63, p < .01) and success rate percentage (rho = 0.74, p < .05) registered during competition. The success rate percentage, in the first half, was observed 44% successes, and in the second half, 59% successes. The number of events called was related with the physical fitness test score (R2 = 0.71, p = .035; R2 = 0.64, p = .056, respectively). As conclusion, the main finding of this study has provided insight into decision-making behavior in real competitive matches and the physical fitness was the predictor of the successful decision-making being able to determine the permanency, promotion or decrease of category.
Keywords: football; referree; physical condition; decision-making; training; JCR